PENGARUH KUALITAS PRODUK TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Rifa Kuliner Kendal) - Cindy Phasalita Widayatma; Sri Puji Lestari (Serat Acitya, 2018)
The purpose of this reseach to determine the effect of product quality on consumer satisfaction, the effect of customer satisfaction on consumer loyalty and the effect of product quality on consumer loyalty and the effect of product quality on consumer loyalty with consumer satisfaction as an intervening variable. The population in this research  were all consumers who bought products from Rifa Culinary in Kendal from November 2017 to January 2018. The sample used was 90 people using non random sampling.  The sampling  technique uses quota sampling, purposive sampling and accidental sampling. Data analysis techniques using multiple regression analysis with intervening ( Path analysis ). The results of the research  show that there is an influence of product quality on customer satisfaction, there is an influence of consumer satisfaction on consumer loyalty and there is an influence of product quality on loyalty with customer satisfaction as an intervening variable.Key words : Product Quality, Consumer Satisfaction, Consumer  Loyalty